2016
DOI: 10.1080/09513590.2016.1193140
|View full text |Cite
|
Sign up to set email alerts
|

Association between anti-Mullerian hormone and insulin resistance in non-obese adolescent females with polycystic ovary syndrome

Abstract: We found that serum AMH levels were higher in non-obese adolescent females with PCOS and IR than in PCOS patients without IR and the healthy controls. There was a significant positive correlation between AMH levels and IR in non-obese adolescent females with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
16
1
1
Order By: Relevance
“…Increased levels of insulin have been shown to cause both a surge in LH and increased androgen release from the theca cells through the ovarian insulin receptors in women with PCOS. Finally, the clinical picture involves the appearance of hyperandrogenaemia, one of the symptoms of PCOS [21920]. However, the relationship between fetuin-A and IR remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of insulin have been shown to cause both a surge in LH and increased androgen release from the theca cells through the ovarian insulin receptors in women with PCOS. Finally, the clinical picture involves the appearance of hyperandrogenaemia, one of the symptoms of PCOS [21920]. However, the relationship between fetuin-A and IR remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although figures vary according to the diagnostic criteria, its incidence is reported to be 6% to 20% [123]. Acne, hirsutism, seborrhoea, menstrual irregularities, anovulation, infertility, obesity, and several metabolic (e.g., glucose and lipid abnormalities) and atherosclerotic disorders are among the symptoms and signs of this disease [45].…”
Section: Introductionmentioning
confidence: 99%
“…Different results have been obtained by various studies conducted in 2 different regions of our country. While Tokmak et al 24 defined a significant correlation between AMH and insulin resistance (IR) among non-obese adolescents, Şahmay et al 25 reported no correlation between AMH and IR. Although there was a weak positive correlation between insulin level and AMH in our study, no correlation between IR, serum fasting glucose and AMH was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pancreatic β-cell dysfunction and Insulin Resistance (IR) are considered to be major biological aspects that lead to the development of type-2 diabetes. Hence, women suffering from PCOS were reported to have higher rates for type-2 diabetes in the long term [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%